2016
DOI: 10.5455/jice.20160416122003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and cytotoxicity properties of the organic solvent fractions of Clerodendrum myricoides (Hochst.) R. Br. ex Vatke: Kenyan traditional medicinal plant

Abstract: Background/Aim:Clerodendrum myricoides is a Kenyan herbal plant used in the management of respiratory diseases. In the current study, we investigated in vitro antimicrobial activity, cytotoxicity, and phytochemical screening of C. myricoidesMaterials and Methods:Antimicrobial activities of C. myricoides organic fractions against array of microorganisms including: (i) Mycobacterium tuberculosis (MTB) H37Rv, (ii) Staphylococcus aureus, (iii) Klebsiella pneumoniae, (iv) Escherichia coli, (v) Candida albicans, (vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…coli Top 10 QS biosensor, and none on the reduction of the expression of GFP, hence, no capacity of QS inhibition. Previous reports on Clerodendrum myricoides have, however, indicated that this medicinal plant does exhibit antimicrobial activity, [ 38 , 39 ] a fact that concurs with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…coli Top 10 QS biosensor, and none on the reduction of the expression of GFP, hence, no capacity of QS inhibition. Previous reports on Clerodendrum myricoides have, however, indicated that this medicinal plant does exhibit antimicrobial activity, [ 38 , 39 ] a fact that concurs with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…There was no indication of mutagenesis when dichloromethane and 70% ethanol extracts were tested on S. typhimurium (Ames test) (TA98) [ 124 ] Clerodendrum myricoides (Hochst.) R.Br.ex Vatke Malaria [ 125 ] Febrile convulsions, Abdominal colic [ 126 ] Respiratory infections [ 37 ] Pneumonia [ 25 ] Antibacterial and antifungal activity (Organic root extract) [ 127 ], antibacterial activity (Aqueous and methanol leaf extract) [ 128 ], antiplasmodial activity (Methanol leaf extract) [ 129 ] in vitro (Agar disc diffusion method) [ 127 ], in vitro (agar diffusion method) [ 128 ], in vivo (Swiss albino mice) [ 129 ] The dichloromethane root bark extract was reported to be nontoxic on L6 cells (IC 50 > 90 µg/mL) [ 130 ]. The methanol root extract was reported to be toxic to brine shrimp [ 131 ] Plectranthus barbatus Andr.…”
Section: Resultsmentioning
confidence: 99%
“…Malaria [125] Febrile convulsions, Abdominal colic [126] Respiratory infections [37] Pneumonia [25] Antibacterial and antifungal activity (Organic root extract) [127], antibacterial activity (Aqueous and methanol leaf extract) [128], antiplasmodial activity (Methanol leaf extract) [129] in vitro (Agar disc diffusion method) [127], in vitro (agar diffusion method) [128], in vivo (Swiss albino mice) [129] The dichloromethane root bark extract was reported to be nontoxic on L6 cells (IC 50 > 90 µg/mL) [130].…”
Section: Rbrex Vatkementioning
confidence: 99%
“…These concentrations were put in sterile bijou bottles and refrigerated at 4 0 C during use. Determination of antibacterial susceptibility patterns was done by the agar disc diffusion method as per Njeru et al with slight modi cations [19]. Gentamycin (40 mcg…”
Section: Antibacterial Assaysmentioning
confidence: 99%